The impact of healthy community environment and sleep quality on the physical health of older adults: evidence from CGSS2021 - Wei, Xiuchao; Dai, Wenwu; Xie, Yue (Frontiers in Psychology, 2025)
As the aging population expands, the proportion of older adults facing physical health challenges is expected to increase substantially. A fundamental question arises as to whether healthy community environment can effectively enhance the physical health of the elderly. This study, based on the 2021 Chinese General Social Survey, included a total of 696 participants aged 65 and above. Our study aimed to investigate the impact of healthy environment, healthy service, and healthy neighborhood on physical health of the elderly, as well as the mediating effects of sleep quality in these relationships. The results are as follows: (1) There were significant positive correlations between healthy environment, healthy service, healthy neighborhood, and sleep quality in pairwise relationships. There was also a significant positive correlation between healthy environment and objective physical health. Similarly, healthy services and healthy neighborhood each had significant positive correlations with subjective physical health, and sleep quality exhibited significant positive correlations with both subjective and objective physical health. (2) After controlling for variables such as gender, age, and perceived socioeconomic status, sleep quality played a mediating role in the relationship between the healthy community geographical environment and physical health of the elderly. The research findings provide empirical evidence for enhancing the physical health of the elderly from the perspective of building a healthy community.